Public health preparedness evaluation and measurement (Italian Journal of Public Health, 2004)
Dear Sir;Public health preparedness refers to the ability of different local, state, and federal entities to carry out a prompt,effective response to any public health threat.[1] Indeed,it is clear that the term “threat”could embracea myriad of elements. Recently, the main focus has been on bioterrorism, defined as the terrorist use of chemical, biological, radiological, nuclear or explosive weapons of mass destruction.However, preparedness also involves other threats such as seasonal influenza epidemics, earthquakes or electricity failures. Programs aimed at improving the level of preparedness of different types of agencies (such as law enforcement, public health agencies, fire services, emergency medical services etc.) in case of terrorist attacks could largely improve the overall ability of the public health system in addressing any threat to health, in particular those related to infectious diseases.